Household fermentation of leftover bread to nutritious food - Hellwig, Coralie; Rousta, Neda; Wikandari, Rachma; Taherzadeh, Mohammad J.; Haggblom-Kronlof, Greta; Bolton, Kim; Rousta, Kamran (Elsevier Ltd, 2022)
Resource dependency of food production is aggravated when food is wasted. In Sweden, it is estimated that 37% of the total bread waste is generated at the household level. This work aimed to assess whether fermentation using edible filamentous fungi at households can provide a solution to valorize leftover bread in the production of fungi-based food for consumption. Bread was fermented in household and laboratory conditions with Neurospora intermedia and Rhizopus oligosporus. The results show that bread can be successfully and easily fermented at households, without signs of microbial contamination even though the conditions were not sterile. Fermentation at the household resulted in higher protein, fat and fiber content as well as greater starch reduction compared to the samples fermented under laboratory conditions. Household engagement in bread fermentation will likely depend on values that motivate reusing leftover bread. Perceived values that are expected to motivate engagement vary across individuals, but may include improved nutritional benefits, food waste prevention, convenience, responsibilities, and being part of sustainable societies and actions.